Comparative plastome analyses and evolutionary relationships of 25 East Asian species within the medicinal plant genus Scrophularia (Scrophulariaceae) - Wang, Xia; Guo, Lei; Ding, Lulu; Medina, Leopoldo; Wang, Ruihong; Li, Pan (Frontiers in Plant Science, 2024)
Scrophularia L., a genus of the Scrophulariaceae, is a group of important medicinal plants used for eliminating heat and detoxifying. East Asia has an abundance of potentially medicinal Scrophularia species, and it serves as a secondary diversity center of the genus. However, the genomic resources available for germplasm identification and pharmaceutical exploration of East Asian Scrophularia are insufficient, hindering its commercial and industrial development. Additionally, the interspecific relationships of most East Asian Scrophularia species remain unclear. Here, we conducted a comparison of plastome information of 25 East Asian Scrophularia species. The conserved plastome length of these 25 species ranged from 151,582 bp to 153,239 bp, containing a total of 132 coding genes, including 18 duplicated genes and 114 unique genes. Through genome alignment of these 25 species, 38-53 repeated sequences and 7 shared SSRs were identified, along with regions with high nucleotide polymorphism (Pi), which could potentially serve as molecular markers for species identification. The genome structure, gene content, and arrangement showed conservation, while variations were observed in the IR boundary regions and IGS. Phylogenetic inferences based on whole plastomes or on coding sequences (CDS) only yielded congruent results. We categorized the 25 East Asian Scrophularia species into six distinct clades and further explored their interspecies relationships using morphological characteristics, such as flower color, the relative position of stamens and corolla, and plant height. This could lay a genetic basis for future resource development of Scrophularia in East Asia.